1998
DOI: 10.1128/jvi.72.1.142-150.1998
|View full text |Cite
|
Sign up to set email alerts
|

The Papillomavirus Minor Capsid Protein, L2, Induces Localization of the Major Capsid Protein, L1, and the Viral Transcription/Replication Protein, E2, to PML Oncogenic Domains

Abstract: We have used immunofluorescent staining and confocal microscopy to examine the subcellular localization of structural and nonstructural bovine papillomavirus (BPV) proteins in cultured cells that produce infectious virions. When expressed separately, L1, the major capsid protein, showed a diffuse nuclear distribution while L2, the minor capsid protein, was found to localize to punctate nuclear regions identified as promonocytic leukemia protein (PML) oncogenic domains (PODs). Coexpression of L1 and L2 induced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
65
0

Year Published

1998
1998
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 175 publications
(65 citation statements)
references
References 55 publications
0
65
0
Order By: Relevance
“…For example, these include HSV-1, ICP0, infected-cell proteins 4 (ICP4), 22 (ICP22), and 27 (ICP27), and products of the CMV UL112-113 gene [11,15,64,[149][150][151]. The localization of viral proteins that facilitate both DNA replication and transcription, as is the case for polyomavirus large T antigen and papillomavirus E2 and E3 proteins, further support a case for VRCs as sites of both viral DNA replication and transcription [11,55,[137][138][139][140]152,153]. In the case of adenovirus, transcription of the viral genomes is believed to occur not within the center of VRCs but rather at their periphery, as evidenced by the localization of cellular factors involved in transcription and RNA biogenesis proximal to VRCs [14,132].…”
Section: Transcriptionmentioning
confidence: 85%
See 1 more Smart Citation
“…For example, these include HSV-1, ICP0, infected-cell proteins 4 (ICP4), 22 (ICP22), and 27 (ICP27), and products of the CMV UL112-113 gene [11,15,64,[149][150][151]. The localization of viral proteins that facilitate both DNA replication and transcription, as is the case for polyomavirus large T antigen and papillomavirus E2 and E3 proteins, further support a case for VRCs as sites of both viral DNA replication and transcription [11,55,[137][138][139][140]152,153]. In the case of adenovirus, transcription of the viral genomes is believed to occur not within the center of VRCs but rather at their periphery, as evidenced by the localization of cellular factors involved in transcription and RNA biogenesis proximal to VRCs [14,132].…”
Section: Transcriptionmentioning
confidence: 85%
“…These virions and tubular structures localized to inter-chromosomal spaces that stain positive for PML and VP1, suggesting that polyomavirus VRCs are the sites of active capsid assembly [55,163]. In the case of papillomaviruses, although the spatial organization of capsid assembly and packaging is not well understood, a number of studies have identified the localization of L1 major and L2 minor capsid protein at VRCs similarly to the localization of polyomavirus capsid proteins [137,152,164].…”
Section: Virion Production At Replication Compartmentsmentioning
confidence: 97%
“…After cell entry, intracellular trafficking through endosomal and Golgi compartments leads to capsid disassembly and release of the L2/HPV genome complex (Bienkowska-Haba et al, 2009b;Cerqueira and Schelhaas, 2012;Florin et al, 2012;Day et al, 2013;Lipovsky et al, 2013;Sapp, 2013). The minor capsid protein L2 chaperones the viral genome into the nucleus and accumulates at subnuclear foci, the PML nuclear bodies (PML-NBs) (Day et al, 1998;Florin et al, 2002a) leading to manifestation of infection, stimulation of cell proliferation, vegetative amplification of the genome, and, finally, viral morphogenesis (Chiang et al, 1992;Florin et al, 2002a;Becker et al, 2004;Day et al, 2004;Doorbar, 2005;Munger et al, 2006;Graham, 2008;Schwartz, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The PML-NBs are composed of PML protein as the main component, and several additional, per se antiviral proteins like Daxx, Sp100 and ATRX (Day et al, 1998;Everett, 2001;Florin et al, 2002b;Everett and Chelbi-Alix, 2007;Tavalai and Stamminger, 2008;Van Damme and Van Ostade, 2011;Wimmer et al, 2012;Stepp et al, 2013). The complex interaction of antiviral proteins in PML-NBs, which on the other side are reported to be highly essential for viral transcription and replication, is closely associated with a group of regulatory proteins known as small ubiquitin-like modifiers (SUMO) (Wimmer et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…In this disorder expression of aberrant ataxin‐1 protein, resulting from mutations in the SCA1 gene, is associated with disruption of the bodies and delocalization of PML, in cerebellar Purkinje cells (Skinner et al , 1997). The nuclear bodies are also targeted by a wide range of viral infections, including herpes simplex, adenovirus, papillomavirus, CMV, EBV, LCMV and HTLV1 (Day et al , 1998; reviewed by Hodges et al , 1998, and references therein). Investigation of the cellular events associated with herpes simplex infection led to the suggestion that PML nuclear bodies could mediate a storage function, harbouring components critical to the progression of infection (Everett & Maul, 1994) and also potentially be involved in transport between nucleus and cytoplasm.…”
Section: Molecular Pathogenesis Of Aplmentioning
confidence: 99%